Choosing a horse : how to choose and care for a horse - Jeffrey, Laura S. (Berkeley Heights, NJ : Enslow Publishers, 2013)
"Discusses the selection, housing, diet, handling, grooming, and health of a new horse"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Horses -- Juvenile literature; Horsemanship -- Juvenile literature